No centro e nas margens: contribuições para atualização dos estudos sobre nação e nacionalismos - Santos Júnior, Natalício Batista dos (2022)
This dissertation addresses the broad spectrum of the subject of nationhood and nationalism in the fields of sociology and politics. The debate surrounding the origins and meanings of the modern nation state is contextualised along historical, geographical, ideological and political dimensions, and reflects the different methodologies, traditions and ruptures of the main contributors to this debate. The question of the nation state and national identity has been the subject of discussions in many related fields within the social sciences and continues to attract attention in academia, government, political parties and social movements. The different interests informing the debate make consensus difficult to establish. Most of the voices informing the debate have been dominated by a Eurocentric perspective. The presence of non-European authors and the analysis of the phenomenon of the nation state and nationalism outside Europe is still practically non-existent. However, the theories and practices of modern colonialism in Europe, Africa, Latin America and Asia must be reassessed in light of what the anti-colonial struggles and nationalist movements located on the periphery of capitalism have contributed. Here the focus has been on the relationship between race and class, modernity and the revolutionary route, as well as the role of indigenous cultures in the formation of national identity. This work considers the contribution made by the Latin-American, Afro-Caribbean and African authors José Carlos Mariátegui, Frantz Fanon and Amílcar Cabral. In their work a number of assumptions are at play: romantic, modernist and Marxist (both orthodox and heterodox). Pioneers in the anti-colonial, anti-imperialist and anti-racist debate, these authors have articulated a critical stance towards Eurocentrism, colonialism and the debate around race and culture, ultimately pointing paths towards a post-colonial update of complex debate around nationhood, nationalism and national identity